Tralokinumab for moderate‐to‐severe atopic dermatitis: results from two 52‐week, randomized, double‐blind, multicentre, placebo‐controlled phase III trials (ECZTRA 1 and ECZTRA 2)*. (1st March 2021) - Wollenberg, A.; Blauvelt, A.; Guttman‐Yassky, E.; Worm, M.; Lynde, C.; Lacour, J.‐P.; Spelman, L.; Katoh, N.; Saeki, H.; Poulin, Y.; Lesiak, A.; Kircik, L.; et al.
Summary: Background: Tralokinumab, a fully human monoclonal antibody, specifically neutralizes interleukin‐13, a key cytokine driving peripheral inflammation in atopic dermatitis (AD). In phase II studies, tralokinumab combined with topical corticosteroids provided early and sustained improvements in AD signs and symptoms. Objectives: To evaluate the efficacy and safety of tralokinumab monotherapy in adults with moderate‐to‐severe AD who had an inadequate response to topical treatments. Methods: In two 52‐week, randomized, double‐blind, placebo‐controlled, phase III trials, ECZTRA 1 and ECZTRA 2, adults with moderate‐to‐severe AD were randomized (3 : 1) to subcutaneous tralokinumab 300 mg every 2 weeks (Q2W) or placebo. Primary endpoints were Investigator's Global Assessment (IGA) score of 0 or 1 at week 16 and ≥ 75% improvement in Eczema Area and Severity Index (EASI 75) at week 16. Patients achieving an IGA score of 0 or 1 and/or EASI 75 with tralokinumab at week 16 were rerandomized to tralokinumab Q2W or every 4 weeks or placebo, for 36 weeks. The trials were registered with ClinicalTrials.gov: NCT03131648 and NCT03160885. Results: At week 16, more patients who received tralokinumab vs. placebo achieved an IGA score of 0 or 1: 15·8% vs. 7·1% in ECZTRA 1 [difference 8·6%, 95% confidence interval (CI) 4·1–13·1; P  = 0·002] and 22·2% vs. 10·9% in ECZTRA 2 (11·1%, 95% CI 5·8–16·4; P  < 0·001) and EASI 75: 25·0% vs. 12·7% (12·1%, 95% CI 6·5–17·7; P  < 0·001) and 33·2% vs. 11·4% (21·6%, 95% CI 15·8–27·3; P  < 0·001). Early improvements in pruritus, sleep interference, Dermatology Life Quality Index, SCORing Atopic Dermatitis and Patient‐Oriented Eczema Measure were observed from the first postbaseline measurements. The majority of week 16 tralokinumab responders maintained response at week 52 with continued tralokinumab treatment without any rescue medication (including topical corticosteroids). Adverse events were reported in 76·4% and 61·5% of patients receiving tralokinumab in ECZTRA 1 and ECZTRA 2, respectively, and in 77·0% and 66·0% of patients receiving placebo in ECZTRA 1 and ECZTRA 2, respectively, in the 16‐week initial period. Conclusions: Tralokinumab monotherapy was superior to placebo at 16 weeks of treatment and was well tolerated up to 52 weeks of treatment.